#TITLE_ALTERNATIVE# - AFFANDI (NIM : 13607049); Dosen Pembimbing : Dr. Ir. Bambang Kismono Hadi; Dr. Ir. Rais Zain, ARIEF
Vertical tail which also called fin, is required to produce aircraft stability when the aircraft in yaw condition. The construction of the vertical tail structure is similar to the horizontal tail. The vertical tail could be made as the integration part of fuselage. Because of the importance of the structure of this vertical tail, then the design of vertical tail structure must be made. Besides that, structure strength analysis must be designed to provide ctritical tail load that can produce an appropiate vertical tail structure. This final project was focussed to design vertical tail structure of fighter MJK. Design of vertical tail structure was done by making study of comparison to the similar fighter and afterwards be matched with the configuration of the fighter MJK. After vertical tail structure has been design with critical load, which occur in asymmetric engine thrust with afterburner, and afterwards analysed by finite element method through to whether the structure of this vertical tail could able to withstand that or not. The results showed that from several structure configuration iterations, maximum stress in the structure was still occure below material strength. This showed that vertical tail structure can able to withstand the critical load.